A short note on the article "Some Applications of the Weak Contraction Principle" (Letters in Nonlinear Analysis and its Applications, 2025)
The purpose of this brief note is to correct and clarify a wrong assertion given in the recent article "Some Applications of the Weak Contraction Principle" [Lett. Nonlinear Anal. Appl. 3 (2025), 1-4], that affects both a valid example used in the article "Remarks on the fixed point theory for quasi-metric spaces" [Results Nonlinear Anal. 7 (2024), 70–74], and two incorrect results presented in the article "All metric fixed point theorems hold for quasi-metric spaces" [Results Nonlinear Anal. 6 (2023), 116–127].
Keywords: Quasi-metric space; fixed point